Peri-Implantitis: A Clinical Update on Prevalence and Surgical Treatment Outcomes - Roccuzzo, Andrea (J Clin Med, 2021)
Dental implants may be considered a reliable routine procedure in clinical practice for the replacement of missing teeth. Results from long-term studies indicate that implant-supported dental prostheses constitute a predictable treatment method for the management of fully and partially edentulous patients. Implants and their restorations, however, are not free from biological complications. In fact, peri-implantitis, defined as progressive bone loss associated to clinical inflammation, is not a rare finding nowadays. This constitutes a concern for clinicians and patients given the negative impact on the quality of life and the sequelae originated by peri-implantitis lesions. The purpose of this narrative review is to report on the prevalence of peri-implantitis and to overview the indications, contraindications, complexity, predictability and effectiveness of the different surgical therapeutic modalities to manage this disorder.